Exploring EFL Students’ Perceptions Toward the Difficulties in Learning English Tenses: Case Study at Tertiary Level - Nailul Rahmadila (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Tenses are a part of grammar that deals with the structure of sentences using specific rules, another essential point is that tenses are used to understand when an event occurs in a spoken or written sentence. As stated by Badroeni et al. (2020), tenses are necessary language construction variables associated with basic sentence structure. Dewi and Marta (2020) added that tenses can be used to indicate if a state, action, or activity is past, present, or future. The English language uses the idea of English tenses to generate effective communication. Hence, as a result, EFL students' comprehension, and competence are needed while selecting the tenses that are appropriate for the sentences and the placement in time. Students might find it difficult to understand English tenses, particularly the complex patterns of the basic tenses, (Wahyuningtyas & Bram, 2018). Therefore, I concentrate on the difficulties that students perceive when learning tenses in an effort that this topic might be further investigated. The research aimed to explore EFL students' perceptions of the difficulties in learning tenses at the tertiary level. I carried out the research at one of the universities in Indonesia including students who are in English Education. The participant criteria for this research were students who had difficulty learning tenses, students who had taken Intermediate English Grammar and Advanced English Grammar courses, students whose grades in the Intermediate English Grammar and Advanced English Grammar courses were low, and students who were willing to be interviewed in this research. The research used a qualitative research design focusing on a descriptive case study. I collected the data by utilizing an interview. Along with this, the semi-structured interview was applied in this research. According to Ruslin (2022), the semi-structured interview gives researchers the flexibility and adaptability to consider the objective of the research while gathering detailed information and evidence from interviewees. Accordingly, the participants were interviewed to explore more about what are students’ difficulties in learning tenses based on their perceptions flexibly. Taken from several reference research from Wahyuningtyas and Bram (2018); Listia and Febriyanti (2020); Ali et al. (2021); and Handayani et al. (2022), it is well-recognized that learning tenses can present some difficulties for students. To make the data discussion more specific and focused, I implemented their findings research as pre-determined themes and guides. Five
Keywords: Tenses; EFL Students’ Perceptions